Military Expenditure and Arms Trade : Alternative Data Sources - Wakeman-Linn, John.; Happe, Nancy (Washington, D.C. : International Monetary Fund, 1994)
Analysis of the economic impact of military expenditures and arms trade is frequently hampered by the limited amount of transparent, comprehensive data. Country-specific information can be supplemented, however, by data from multicountry statistical sources. This paper describes seven publications which provide multicountry statistics on military expenditure and trade--the information each source conveys, as well as the differences in coverage and definition--to assist the analyst in understanding how to use this data. Comparisons of the data reported by the various sources reveal numerous, significant differences, particularly in data on military expenditures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States